University History in the Czech Republic - Fasora, Lukáš; Hanuš, Jiří (CIAN-Revista de Historia de las Universidades, 2017)
This text provides a historiographical overview of research into university history in the Bohemian lands. The authors point to the limited standing that the specialized discipline of university history has within Czech historiography, and summarize the methodological difficulties which prevent this discipline from gaining more respect. This is mainly due to it being too closely connected with anniversaries and, consequently, the uncertain existence of research teams. From a methodological perspective, this organizational problem results in the over-representation of institutional biographies in the portfolio of studies, while a greater proportion of the publications interpret university history in isolation from the rest of the society and are a priori success stories. It has only been over the past two decades that there have been changes in the discipline which have rapidly brought it up to speed in methodological terms with other, more traditional historical disciplines. The text also focuses on an overview of important, breakthrough works in the discipline and their place within socio-political changes, with special attention paid to the oldest Czech university in Prague, though there is also an examination of interesting trends in the research into the history of newer, provincial Czech universities.
Keywords: university history; Bohemian lands; historiographical overview